Analysis the Implementation of Independent Learning-Independent Campus Program based on Students’ Perceptions - Sahid Sahid; Rosidah Rosidah; Baharuddin Baharuddin (EduLine: Journal of Education and Learning Innovation, 2024)
Investigations of the independent learning-independent campus program still encounter obstacles in its implementation. This research is research that is motivated by the phenomenon of certain obstacles and problems faced by students when implementing independent learning-independent campus program in the mathematics department, FMIPA UNM, so it needs to be reviewed and carried out further analysis as material for further improvements. This research aims to explore student perceptions regarding the implementation of independent learning-independent campus program which is focused on the implementation of existing programs at independent learning-independent campus program which is implemented in the Mathematics Department of FMIPA UNM. This research is quantitative descriptive research using survey methods. The research was carried out at the Mathematics Education Study Program, Department of Mathematics, Faculty of Mathematics and Natural Sciences, State University of Makassar. The sample in this study were students in semester IV and semester VI from the FMIPA mathematics department who were selected purposively based on research interests and needs, namely students who took part in the independent learning-independent campus program. Data was analyzed descriptively to see students' perceptions of the implementation of the independent learning-independent campus program. Research finds that students majoring in mathematics at FMIPA UNM responded well to the MBKM program, it can be seen that the majority of students were interested in joining the program.